Perceptions of followership among nurses: A qualitative study - Sulaiman Alanazi; Richard Wiechula; David Foley (Elsevier, 2024)
Background: Followership is defined as the role individuals play in supporting, contributing to, and realizing the vision and directives set by their leaders. Such a role is indispensable in healthcare, facilitating effective team dynamics and healthcare delivery. Within the nursing field, it encompasses nurses' active engagement and participation in healthcare delivery, ensuring safety, fostering teamwork, and enhancing patient outcomes. Despite its significance, the exploration of followership within the nursing context of Saudi Arabia remains limited. Objective: This study aims to explore how followership is perceived and practiced by nurses in this unique cultural and professional setting, and its implications for healthcare delivery. Methods: We conducted a qualitative inquiry involving seven registered nurses working in hospitals affiliated with the Saudi Arabian Ministry of Health. Semi-structured interviews were conducted, and a thematic analysis was utilized to extract key findings. Results: Our thematic analysis identified four main themes and several sub-themes that encapsulate the participants' perspectives on followership. The themes include: (1) Understanding of followership, where a predominant lack of clarity about the concept was observed, often conflating it with teamwork; (2) Followers' involvement in decision-making, highlighting the limited participation of nurses in decision-making processes due to hierarchical and autocratic leadership structures; (3) Barriers to followership, which encompassed issues such as poor leadership, the undervaluation of the follower role, lack of training and development opportunities, challenges in collaboration, and language barriers; and (4) Facilitators of followership, identified as effective leadership, followership training, communication skills, positive relationships, respect, collaboration, understanding of roles, commitment, and flexibility. These findings elucidate the complex landscape of followership within the nursing profession in Saudi Arabia, revealing both the challenges and pathways to fostering effective followership in healthcare settings. Conclusion and Implications: This study reveals a widespread lack of awareness about followership among nurses in Saudi Arabia, highlighting significant challenges related to hierarchy and the undervaluation of the follower role in nursing practice and education. It underscores the need for educational and training interventions that redefine and elevate the role of followership in clinical settings to enhance collaboration, assertiveness, and decision-making skills. Moreover, the study advocates for the re-evaluation of leadership practices to better acknowledge and value followership, promoting a more flattened hierarchy that encourages active participation in patient care and organizational development. Implementing these changes could improve patient outcomes and increase nurse satisfaction by effectively addressing the identified barriers related to hierarchy and leadership.